2007
DOI: 10.1038/sj.bjc.6603962
|View full text |Cite
|
Sign up to set email alerts
|

Decreased number of mast cells infiltrating into needle biopsy specimens leads to a better prognosis of prostate cancer

Abstract: Mast cell infiltration is often observed around human tumours. Inflammatory cells such as macrophages, neutrophils and mast cells infiltrating around tumours are known to contribute to tumour growth; however, the clinical significance of mast cell invasion in prostate cancer (PCa) has not been investigated. Mast cell infiltration was evaluated in 104 patients (age range, 45 -88 years; median, 72 years), who underwent needle biopsy of the prostate and were confirmed to have PCa. Needle biopsy specimens of prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
85
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 42 publications
(39 reference statements)
9
85
2
2
Order By: Relevance
“…This could explain the contradictory findings regarding mast cell function in PC by other researchers [12][13] and are in line with the described plasticity of the role of mast cells in tumor biology. 8 -11 Mast cells produce a broad repertoire of cytokines to regulate inflammatory responses, growth factors to stimulate blood vessels and fibroblasts, and enzymes capable of releasing growth factors from extracellular matrix.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…This could explain the contradictory findings regarding mast cell function in PC by other researchers [12][13] and are in line with the described plasticity of the role of mast cells in tumor biology. 8 -11 Mast cells produce a broad repertoire of cytokines to regulate inflammatory responses, growth factors to stimulate blood vessels and fibroblasts, and enzymes capable of releasing growth factors from extracellular matrix.…”
Section: Discussionsupporting
confidence: 56%
“…[12][13] In both nonmalignant and malignant human prostate tissue, mast cells were found principally in the stroma. In prostate tumors only a few mast cells were detected in the epithelial compartment ( Figure 4, A and B).…”
Section: Mast Cells Are Located In the Prostate Stroma In Menmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the frequency of Foxp3 + cells with low cell surface CD25 was similar in the tumor and marginal tissue ( CRC Tumors Are Enriched in MC. Numerous reports exist of accumulation of MC in tumors, but only recently has this accumulation been convincingly linked with poor prognosis (22,23) and experimentally associated with carcinogenesis (4-6), as reviewed elsewhere (2, 3). Our earlier study suggested that there is a 3-fold enrichment of MC in human polyps compared with marginal tissue (4).…”
Section: Resultsmentioning
confidence: 99%
“…While this manuscript was under review, Soucek et al (58) reported that MC are required for the expansion of myc-induced pancreatic tumors, and Nonomura et al (59) reported a positive correlation between the frequency of MC in human prostate cancer needle biopsy specimens and poor prognosis.…”
Section: Cd34mentioning
confidence: 99%